Adopting Digital Technologies into Urban Settings: Towards Smarter Cities and Better Quality of Life - Berawi, Mohammed Ali; Miraj, Perdana; Sari, Mustika (CSID Journal of Infrastructure Development, 2019)
Major cities worldwide are now experiencing immense growth caused by rapid urbanization and industrialization over the past decades. Currently, more than half of the world’s population lives in the urban area and this number is projected to increase most likely to more than 65% by 2050. Nowadays, Asia has the highest number of urban dwellers, which subsequently followed by Europe and Africa. Back in 2000, Tokyo was the largest metropolitan area occupied by 37 million citizens, followed by New Delhi, Shanghai, Mexico City, and Sao Paulo. Other cities such as Cairo, Mumbai, Beijing, and Dhaka caught up with average inhabitants of around 20 million people. Urbanization has been recognized as the driver that has given a huge contribution that helps increase the economic development in urban cities on a global scale. Despite its positive influences for economic growth, urbanization has led to various urban challenges including but not limited to congestion, urban sprawl, environmental degradation, limited job opportunities, housing, and public safety. Along with the rise of information and communication technology (ICT) that is developing rapidly and disruptively in the past few years, traditional cities are changing by adopting the smart city concept aiming to address both its existing problems and future challenges. Even though there is no consensus yet among academics and policymakers about the definition of smart city concept, most of them agreed that smart city is a city development and management by considering the adoption of ICT in order to connect, monitor, and control various resources inside the city in an efficient and effective manner to optimize services for the people in performing their daily activities and to address the urban challenge. In general, a smart city should be seen more as an integrated system of sensors and processors integrated within the city’s infrastructure network rather than the employment of ICT specifically in a particular city domain. The concept of a smart city is currently presented as the solution to urban challenges by coming up with new innovations to solve the mounting problems faced by urban cities to make cities better connected and more efficient in terms of connection, coordination, usage of resources, resiliency and sustainability. Published at: CSID - JID Vol 2, No 2 (2019)